Power and Resistance in the Dialogues of Mickey 17 (2025): A Critical Discourse Analysis - Bhoko , Ekarestia Eufrosina (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study investigates the representation of power and resistance in the dialogues of Bong Joon-ho’s science fiction film Mickey 17 (2025) using Critical Discourse Analysis (CDA). The research aims to examine how linguistic choices in the film construct ideological tensions between corporate authority and human agency within a dystopian narrative. Employing a qualitative descriptive approach, the study analyzes selected dialogues using Fairclough’s three-dimensional CDA model, which integrates textual analysis, discourse practice, and sociocultural context. The data consist of dialogue excerpts from key scenes involving the protagonist, corporate representatives, and colonists, representing different positions within the film’s power hierarchy. The analysis focuses on linguistic features such as modality, imperative forms, pronoun usage, and speech acts. The findings reveal that power is discursively constructed through authoritative language, contractual discourse, and hierarchical pronoun use that normalize obedience and legitimize human disposability. In contrast, resistance is articulated through refusal, irony, and discursive questioning, allowing subordinate characters to challenge dominant ideology within constrained communicative spaces. These linguistic strategies reflect broader socio-political discourses on labor exploitation, technological control, and the commodification of human life. The study concludes that dialogue in Mickey 17 functions as a crucial site of ideological negotiation, where power is both enacted and contested through language. By applying CDA to a contemporary science fiction film, this research contributes to media linguistics and film discourse studies, demonstrating how popular cinema encodes and critiques power relations through everyday linguistic practices.